Acute Attack of Pseudogout with the Wide Lesion in Lumbar Spondylolytic Spondylolisthesis - Hironari Kaneyama; Yuichiro Morishita; Osamu Kawano; Takuaki Yamamoto; Takeshi Maeda (Case Reports in Orthopedics)
Objective. To report a rare case of an acute attack of calcium pyrophosphate dihydrate (CPPD) deposition disease in a patient with lumbar spondylolytic spondylolisthesis, which demonstrated widespread lesion with neurological deficit. Methods. An 86-year-old woman presented with high fever and bilateral neurological deficit of the lower extremities. Results. CRP was elevated (20.9 mg/dl). Plain radiographs and computed tomography images showed bilateral L4 spondylolytic spondylolisthesis. Sagittal magnetic resonance (MR) images revealed effusion at the L3-4 interspinous space, and a gadolinium- (GD-) enhanced epidural mass was observed at the level of L4 vertebral body. Axial MR images showed an intra- or epidural lesion at L2-3. Moreover, epidural GD-enhanced masses compressed the dural sac in the shape of a cross at the L3-4 and L4-5 segments. The patient was suspected of having pyogenic arthritis of the lumbar spine in initial diagnosis. A total of 1.2 ml of fluid with a murky, pus-like synovial effusion was aspirated from the L3-4 interspinous space under the fluoroscopic image. Smear speculum of synovial fluid tested negative for bacteria and fungi; however, a number of crystals were seen. Based on the result of smear speculum, we suspected the pathology as crystal deposition disease. Based on polarized light microscopy, which revealed monocle or triclinic intracellular crystals with a positive birefringence, the patient was diagnosed with pseudogout of the lumbar spine. Nonsteroidal anti-inflammatory drugs (NSAIDs) were administered by intravenous drip injection for 3 days, and local and systemic inflammatory signs, as well as neurological deficits, dramatically improved. Conclusions. We encountered the rare case of an acute attack of pseudogout with the wide lesion in the lumbar spondylolytic spondylolisthesis. Multiple culture of the effusion provided a definitive diagnosis, which allowed for appropriate, minimally invasive treatment for 8 weeks of NSAID administration that provided the satisfactory recovery from the symptoms.